Accumbal ghrelin and glucagon-like peptide 1 signaling in alcohol reward in female rats. Issue 12 (15th August 2018) - Abtahi, Shayan; Howell, Erin; Currie, Paul J.
Abstract : The present study investigated the relationship between accumbal ghrelin and glucagon-like peptide 1 (GLP-1) signaling in alcohol reward in female rats. Animals with guide cannulae targeting the nucleus accumbens core (NAcC) and shell (NAcS) were habituated to alcohol for 12 weeks through a two-bottle intermittent access paradigm. JMV2959, a ghrelin antagonist, and exendin-4 (Ex-4), a GLP-1 agonist, were microinjected at the onset of the nocturnal cycle. Alcohol, food, water, and total fluid intake were measured 2, 6, and 24 h postinjection. Results indicated that JMV2959 reduced alcohol consumption when injected into both the NAcC and NAcS. Ex-4 administration as well as combined JMV2959 and Ex-4 treatment reduced intake when injected into the NAcS, but not the NAcC. These effects were time-dependent. JMV2959 had no effect on food intake when administered into either the NAcC or the NAcS, whereas Ex-4 decreased food intake when injected separately into both structures. The combination of JMV2959 and Ex-4 decreased food intake when administered only into the NAcC. These effects were also time-dependent. No estrous-related effects on alcohol or food intake were found. However, water and total fluid intake were increased during the metestrus and diestruses phases of the estrous cycle compared with the proestrus and estrus phases. Overall, these findings demonstrate the importance of accumbal ghrelin and GLP-1 signaling in alcohol reward and appetitive motivation.